Upaya Penanggulangan Stunting di Nagari Kapuh, Pesisir Selatan: Edukasi Gizi dan Perubahan Perilaku - Yayuk Lestari; Meqorry Yusfi; Annisa Anindya; Vitania Yulia; Diego Diego (I-Com: Indonesian Community Journal, 2024)
Stunting is a serious public health issue in Indonesia, especially at Nagari Kapuh, Koto XII Tarusan District, Pesisir Selatan region of West Sumatera. The survey results revealed that 32 out of 59 children are experiencing stunting. This condition is influenced by several factors, including poor nutritional intake, limited capacity of posyandu (community health post) volunteers and the damaged medical equipment. Addressing this issue requires a holistic and collaborative approach. Efforts include providing education on balanced nutrition, training posyandu volunteers to improve their monitoring and nutrition counseling skills. Improving healthcare facilities and encouraging participation are also crucial steps in combating stunting in this area. It is hoped that through strong collaboration between various stakeholders—including, village authorities, and relevant institutions—the stunting rate in Nagari Kapuh can be significantly reduced. This program aims both to lower the prevalence of stunting and to improve the overall quality of life for the community.